Novel triadimenol detection assay based on fluorescence resonance energy transfer between gold nanoparticles and cadmium telluride quantum dots. (February 2018) - Liu, Guangyang; Huang, Xiaodong; Zheng, Shuning; Li, Lingyun; Xu, Donghui; Xu, Xiaomin; Zhang, Yanguo; Lin, Huan
Abstract: We developed a highly sensitive fluorescent assay based on fluorescence resonance energy transfer (FRET) between gold nanoparticles (AuNPs) and cadmium telluride (CdTe) quantum dots (QDs) for detection of triadimenol in tap water and agricultural irrigation water. The electrostatic interaction between the positively charged CdTe QDs and negatively charged AuNPs strongly quenched the fluorescence emission of CdTe QDs. In the presence of triadimenol, the strong electrostatic attraction between negatively charged AuNPs and positively charged triadimenol molecules rapidly induced the aggregation of AuNPs, blocking the FRET reaction and attenuating the quenched efficiency of CdTe QDs. The change of fluorescence intensity was linearly related to the concentration of triadimenol in the concentration range of 0.338–33.8 μM. The detection limit (S/N = 3) of the sensor was as low as 0.182 μM. The fluorescent sensor was successfully used to detect triadimenol in spiked water samples and gave good recoveries. Graphical abstract: Highlights: Fluorescent assay for triadimenol detection in irrigation water was developed. Electrostatic attraction between AuNPs and triadimenol induced AuNPs aggregation. FRET reaction between AuNPs and CdTe QDs was blocked by electrostatic attraction. Fluorescence intensity changes were linearly related to the triadimenol concentration. The detection limit (S/N = 3) of the assay was as low as 0.182 μM.